How did revenue diversification affect bank performance in emerging economies during the financial crisis? - Hoang Thi Linh, Chi (My University, 2014)
This study examines the impact of revenue diversification on bank performance in group E7 including seven largest emerging countries during financial crisis from 2007 to 2010. They are Brazil, China, Indonesia, India, Mexico, Turkey and Russia. The tests are executed to investigate whether revenue diversification strategy offers better risk-return tradeoffs and therefore boost performance and greater safety for these emerging banking industries. The thesis documents the increase of non-interest income at those banks in the period of time, and then assesses the financial implications of changes by evaluating diversification and risk-adjusted return measurement. Multiple regressions analyses using cross-sectional regressions and fixed effects regressions on panel data are applied. Evidence suggests that diversiﬁcation beneﬁts exist in emerging banks during financial crisis, and these gains have been offset by the increased exposure to non-interest activities. The diversification benefits are also found in individual banks over time. The findings also reveal that revenue diversification effect is non-linear with risk and it is conditioned by the risk level. Moreover, empirical diversification is seen to be not homogeneous across bank specific pillars. Interestingly, it apparently indicates that the diversification effect is found to positive and quantitatively large for other-bank category, comparatively less benefits for commercial banks, and insignificant prosperity for investment banks and cooperative banks. Finally, empirical findings prove that banks which are large and well-capitalized have more incentives to diversify.
Keywords: Revenue diversification; non-interest income; bank performance; emerging economies; fi=Master's Degree Programme in Finance|